Alterations in the tear film and ocular surface in pediatric migraine patients - Aşık, Abdulvahit; Aksoy Aydemir, Gözde; Aydemir, Emre; Bilen, Abdurrahman; İpek, Rojan; Ballı, Hacı; Bayat, Alper Halil; Aydın Türk, Bilge (My University, 2024)
Purpose: To evaluate the ocular surface (OS) parameters in the pediatric migraine patients (PMPs). Methods: This prospective case–control study consisted of 51 PMPs (PMP group) and 55 healthy pediatric patients (HPP group). In all participants, tear function was evaluated subjectively using the Ocular Surface Disease Index (OSDI) questionnaire, objectively using Schirmer tear test (STT) and tear film disintegration time (TBUT), and with clinical and laboratory examinations (conjunctival impression cytology). The PMP group was subdivided into two groups according to their aura. Results: The mean age and gender distribution of the study groups were almost the same (P > 0.05 for both of them). In the PMP group, both the STT value and the TBUT value were significantly lower than those determined in the HPP group (P = 0.021 and P = 0.018, respectively). In the PMP group, the OSDI scores were higher than those in the HPP group (P = 0.032). In the PMP group, the goblet cell density values were lower than those in the HPP group (P = 0.01). With regard to the aura, the TBUT and STT values were nonsignificantly lower in the PMP aura?positive group than in the PMP aura?negative group (P > 0.05 for both of them). The OSDI assessment was similar in both the groups. With regard to the goblet cell count, it was observed to be less in the PMP aura?positive group than in the PMP aura?negative group (P = 0.01). Conclusion: Influence of OS in children with migraine was also demonstrated using the samples taken from the conjunctiva. These changes were also demonstrated by objective tests such as STT and TBUT. Both clinical objective evaluations and pathologic changes were more prominent in the migraine with aura group.
Keywords: Conjunctival Impression Cytology; Dry Eye Diseases; Headache; Pediatric Migraine